Lived Experiences of Women Leaders in a Male-dominated World of Work: A Phenomenological Study - Victoria Q. Paraggua; Ma. Nissa C. Espiritu; Ellen E. Luna (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2022)
The maritime industry is still considered to be a male-dominated field. Nevertheless, there are a few women who still managed to emerge victorious in the field, defying the stigma that women cannot embrace the maritime world. This phenomenological study focuses on the lived experiences of women leaders in the maritime field while ascending to their current position. It utilized a researcher-made semi-structured interview guide about the journey of each participant to leadership. Eight participants were purposively selected to shed light on the matters being sought. This study also clustered the challenges these women leaders individually encountered as they rose from the ranks. Values and principles which helped and guided the participants to triumph over the challenges were also discussed. Job excellence is common among the participants as their way to overcome any challenge. They eventually gained the respect of their male colleagues by proving their worth and doing their best.